A relentless rake ebook - Harrington, Anna (Lords of the Armory, 2022)
"Un-put-downable... This may be Harrington's best yet." —Publisher's Weekly STARRED Review For fans of Grace Burrowes, Sarah Maclean, and Bridgerton, USA Today bestselling author Anna Harrington brings you a sexy feminist historical romance with: An unapologetic rake attempting to cover up his past A rule-following heroine unafraid to speak her mind Thrilling action and mystery Passionate attraction that overrides their deepest resistance Notorious rake Alexander Sinclair, Earl of St James, takes pride in displaying his sins. When he's tasked by the Home Office with finding the men who attempted to assassinate the prime minister, his hunt leads him to Olivia Everett, a most proper schoolmistress who wants nothing to do with a profligate nobleman like him. Unknown to her, Olivia's brother Henry has been working with the revolutionary group planning to overthrow the government. Shocked and hoping to save her brother, Olivia agrees to help the persuasive earl. But the closer they get to uncovering the villains, the more Alec and Olivia will need to trust each other. Praise for Anna Harrington: "As steamy as it is luscious. My favorite kind of historical!"— Grace Burrowes , New York Times bestselling author, for Dukes Are Forever "A touching and tempestuous romance, with all the ingredients Regency fans adore."— Gaelen Foley , New York Times bestselling author, for Dukes Are Forever "Harrington is a rising star...plenty of both love and danger."—Booklist STARRED Review for An Inconvenient Duke